2018
DOI: 10.1645/17-173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection ofTheileria annulatain Cattle from Different Regions of Punjab, Pakistan, by Using Recombinase Polymerase Amplification and Polymerase Chain Reaction

Abstract: Piroplasmosis is one of the most important diseases of livestock, constraining optimal production and leading to economic loss. This study was carried out to detect Theileria annulata by using 2 different molecular techniques: recombinase polymerase amplification (RPA) and conventional polymerase chain reaction (PCR). Blood samples were collected from 274 ticks infesting asymptomatic cattle from several counties in the Chakwal, Faisalabad, and Jhang districts of Punjab Province in Pakistan by using FTA cards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Concurrently, research should also be focused on unexplored areas of population genomics of TTBPs using high-throughput techniques such as NGS and microfluidics. As discussed earlier, the current focus of research is on the control of TTBDis of large ruminants in this country [72,119,[160][161][162], however, in a predominantly mixed-species farming system where small and large ruminants are reared together, sheep and goats could serve as alternative hosts for TTBPs of large ruminants [163,164]. Therefore, for the effective control of TTBDis of livestock in Pakistan, it is imperative to design future studies including common livestock species that are kept in proximity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Concurrently, research should also be focused on unexplored areas of population genomics of TTBPs using high-throughput techniques such as NGS and microfluidics. As discussed earlier, the current focus of research is on the control of TTBDis of large ruminants in this country [72,119,[160][161][162], however, in a predominantly mixed-species farming system where small and large ruminants are reared together, sheep and goats could serve as alternative hosts for TTBPs of large ruminants [163,164]. Therefore, for the effective control of TTBDis of livestock in Pakistan, it is imperative to design future studies including common livestock species that are kept in proximity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, previous studies were confined to the surrounding areas of major metropolitan cities without considering diverse climatic conditions and bovine production systems in Pakistan which are important factors in the design of epidemiological studies [7]. Recently, several studies have utilized molecular methods for the detection of pathogens in bovines [30, 31] and their ticks [18]. However, these studies only targeted the main TBPs pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gebrekidan et al [ 20 ] reported the presence of T. orientalis in Pakistan for the first time from imported and native animals, reporting no T. orientalis in native animals by conventional PCR and low prevalence (6%) in native cattle as compared with imported animals (25.4%) using multiplexed tandem PCR. Recently, Hassan et al [ 21 , 22 ] determined the presence of Theileria spp. by using recombinase polymerase amplification.…”
Section: Introductionmentioning
confidence: 99%